Bacterial etiology and antimicrobial resistance in bloodstream infections at the University of Gondar Comprehensive Specialized Hospital: a cross-sectional study - Deress, Teshiwal; Belay, Gizeaddis; Ayenew, Getahun; Ferede, Worku; Worku, Minichil; Feleke, Tigist; Belay, Solomon; Mulu, Meseret; Adimasu Taddese, Asefa; Eshetu, Tegegne; Tamir, Mebratu; Getie, Michael (Frontiers in Microbiology, 2025)
BackgroundBacterial bloodstream infections are a major global health concern, particularly in resource-limited settings including Ethiopia. There is a lack of updated and comprehensive data that integrates microbiological data and clinical findings. Therefore, this study aimed to characterize bacterial profiles, antimicrobial susceptibility, and associated factors in patients suspected of bloodstream infections at the University of Gondar Comprehensive Specialized Hospital.MethodsA cross-sectional study analyzed electronic records from January 2019 to December 2021. Sociodemographic, clinical, and blood culture data were analyzed. Descriptive statistics and binary logistic regression were employed to identify factors associated with bloodstream infections. Descriptive statistics such as frequency and percentage were computed. Furthermore, a binary and multivariable logistic regression model was fitted to determine the relationship between BSI and associated factors. Variables with p-values of <0.05 from the multivariable logistic regression were used to show the presence of statistically significant associations.ResultsA total of 4,727 patients’ records were included in the study. Among these, 14.8% (701/4,727) were bacterial bloodstream infections, with Gram-negative bacteria accounting for 63.5% (445/701) of cases. The most common bacteria were Klebsiella pneumoniae (29.0%), Staphylococcus aureus (23.5%), and Escherichia coli (8.4%). The study revealed a high resistance level to several antibiotics, with approximately 60.9% of the isolates demonstrating multidrug resistance. Klebsiella oxytoca, Klebsiella pneumoniae, and Escherichia coli exhibited high levels of multidrug resistance. The study identified emergency OPD [AOR = 3.2; (95% CI: 1.50–6.74)], oncology ward [AOR = 3.0; (95% CI: 1.21–7.17)], and surgical ward [AOR = 3.3; (95% CI: 1.27–8.43)] as factors associated with increased susceptibility to bloodstream infections.ConclusionThe overall prevalence of bacterial isolates was high with concerning levels of multi-drug resistance. The study identified significant associations between bloodstream infections with age groups and presentation in specific clinical settings, such as the emergency OPD, oncology ward, and surgical ward. Strict regulation of antibiotic stewardship and the implementation of effective infection control programs should be enforced.